2015
DOI: 10.18632/oncotarget.4216
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib is effective in pancreatic cancer with epidermal growth factor receptor mutations: a randomized, open-label, prospective trial

Abstract: ObjectiveTo analyze the efficacy of gemcitabine with or without erlotinib for pancreatic cancer, and to determine the predictive role of epidermal growth factor receptor (EGFR) and KRAS mutations in these patients.MethodsThis was a single-center, randomized, open-label, prospective trial. Eighty-eight chemotherapy-naïve metastatic pancreatic cancer patients were randomized for treatment with gemcitabine or gemcitabine plus erlotinib. EGFR and KRAS mutations were analyzed, respectively. The primary endpoint was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 40 publications
4
67
2
1
Order By: Relevance
“…57 A more-recent randomized trial conducted in Taiwan reported a median overall survival of 7.2 months in patients treated with erlotinib plus gemcitabine versus 4.4 months among those treated with gemcitabine alone. 58 …”
Section: Mapk Pathway Inhibitorsmentioning
confidence: 99%
“…57 A more-recent randomized trial conducted in Taiwan reported a median overall survival of 7.2 months in patients treated with erlotinib plus gemcitabine versus 4.4 months among those treated with gemcitabine alone. 58 …”
Section: Mapk Pathway Inhibitorsmentioning
confidence: 99%
“…Considering this, EGFR targeted therapies can be rescued in PDAC patients whose tumours bearing wild type KRAS and overexpressing EGFR. Evidently, in a randomized, open-label, prospective trial, adjuvant cemotherapy gemcitabine plus erlotinib was found to be more effective than gemcitabine alone for treating metastatic PDAC, especially those with EGFR mutations (ClinicalTrials.gov number, NCT01608841) [264].…”
Section: Use Of Biomarkers To Guide Therapymentioning
confidence: 99%
“…In recent years, targeted therapies have been tested for treating metastatic pancreatic cancer, for example Erlotinib, an inhibitor of the epidermal growth factor receptor (EGFR) (ClinicalTrials.gov number NCT01608841), is a successful example of how using an antibody, in combination with gemcitabine-based chemotherapy, is effective in improving overall and progression-free survival, as well as response rates in metastatic PDA patients [6].…”
Section: Alpha-enolase (Eno1) and Anti-eno1 Antibody-based Immunotherapymentioning
confidence: 99%